The first records of quill mites of the family Syringophilidae (Acariformes: Prostigmata: Cheyletoidea) from trogoniform birds (Aves: Trogoniformes) - Skoracki, Maciej; Mironov, Sergey V.; Unsoeld, Markus (Zootaxa, 2013)
Two new species of quill mites of the family Syringophilidae parasitising trogoniform birds (Trogoniformes: Trogonidae) are described: Syringophiloidus quetzali sp. nov. from Pharomachrus mocinno Llave and Ph. antisianus (Orbigny); and Syringophilopsis trogoni sp. nov. from Trogon citreolus Gould and T. melanocephalus Gould. These findings are the first records of syringophilids associated with trogoniform birds.